Priming of LTP in amygdala and hippocampus by prior paired pulse facilitation paradigm in mice lacking brain serotonin. Issue 7 (7th December 2018) - Gebhardt, Christine; Mosienko, Valentina; Alenina, Natalia; Albrecht, Doris
Abstract: This study focuses on analyzing long‐term potentiation (LTP) changes in the lateral nucleus of the amygdala (LA) and in the CA1 region of the hippocampus in slices derived from mice deficient in tryptophan hydroxylase 2 (TPH2 −/− ), the rate‐limiting enzyme for 5‐HT synthesis in the brain. We found a reduced LTP in both brain structures in TPH2 −/− mice. However, we found no changes in the magnitude of LTP in TPH2 −/− mice compared to wildtype mice when it was preceded by a paired pulse protocol. Whereas the magnitude of long‐term depression (LTD) did not differ between wildtype and TPH2 −/− mice, priming synapses by LTD‐induction facilitated subsequent CA1‐LTP in wildtype mice to a greater extent than in TPH2 −/− mice. In the LA we found no differences between the genotypes in this protocol of metaplasticity. These data show that, unlike exogenous 5‐HT application, lack of 5‐HT in the brain impairs cellular mechanisms responsible for induction of LTP. It is supposed that suppression of LTP observed in TPH2 −/− mice might be compensated by mechanisms of metaplasticity induced by paired pulse stimulation or low frequency stimulation before the induction of LTP.